2015
DOI: 10.1111/jcmm.12662
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of different HER‐2 mutations in breast cancer progression and drug resistance

Abstract: Studies over the last two decades have identified that amplified human epidermal growth factor receptor (HER‐2; c‐erbB‐2, neu) and its overexpression have been frequently implicated in the carcinogenesis and prognosis in a variety of solid tumours, especially breast cancer. Lots of painstaking efforts were invested on the HER‐2 targeted agents, and significantly improved outcome and prolonged the survival of patients. However, some patients classified as ‘HER‐2‐positive’ would be still resistant to the anti‐HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 115 publications
(186 reference statements)
1
44
0
Order By: Relevance
“…Cancer cells can become resistant to antibodies due to genetic mutations, leading to innate or acquired resistance towards the treatment, as seen for the use of Herceptin to treat HER2 positive breast cancers. [54,55] Additionally, the present study has shown enhanced cell kill compared to previous work where other carbohydrates have been used for selective cancer targeting. [13,15] More importantly, we have successfully increased levels of cell death with lower irradiation periods and radiation doses (29 mW/cm 2 ; 10.5 J/cm 2 for 6 minutes) to those reported previously (50 mW/cm 2 ; 90 J/cm 2 for 30 minutes).…”
Section: Discussionsupporting
confidence: 47%
“…Cancer cells can become resistant to antibodies due to genetic mutations, leading to innate or acquired resistance towards the treatment, as seen for the use of Herceptin to treat HER2 positive breast cancers. [54,55] Additionally, the present study has shown enhanced cell kill compared to previous work where other carbohydrates have been used for selective cancer targeting. [13,15] More importantly, we have successfully increased levels of cell death with lower irradiation periods and radiation doses (29 mW/cm 2 ; 10.5 J/cm 2 for 6 minutes) to those reported previously (50 mW/cm 2 ; 90 J/cm 2 for 30 minutes).…”
Section: Discussionsupporting
confidence: 47%
“…22 It is interesting to note that ERBB2mut when accompanying ERBB2amp has been cited as a potential acquired resistance mechanism for patients with HER2-positive disease originally detected by IHC and/or FISH and currently progressing on standard anti-HER2 targeted therapies. 38 The most frequently altered genes in this series of ERBB2mut breast cancers included TP53 (49%) and PIK3CA (42%). This TP53 mutation frequency is higher than that published for primary breast cancer and the enrichment may reflect the fact that all the patients had stage IV disease at the time of sequencing 34 and that TP53 missense mutation is a negative prognostic factor for breast cancer.…”
Section: Original Articlementioning
confidence: 77%
“…It has been theorized that anti‐HER2 antibody therapeutics such as trastuzumab and pertuzumab may be useful in the treatment of ERBB2 mut tumors, especially when the mutation is within the ECD and causing enhanced dimerization of the HER2 and HER3 proteins . It is interesting to note that ERBB2 mut when accompanying ERBB2 amp has been cited as a potential acquired resistance mechanism for patients with HER2‐positive disease originally detected by IHC and/or FISH and currently progressing on standard anti‐HER2 targeted therapies …”
Section: Discussionmentioning
confidence: 99%
“…Recently, data from preclinical and clinical studies have attributed somatic mutations in HER2, a role in the constitutive expression [31][32][33] or differential regulation of HER2 that leads to resistance (primary or acquired) to anti-HER2 therapy and endocrine therapy [4,6,10,[34][35][36]. Such mutations therefore undermine the clinical benefits of HER2-targeted treatment in HER2-positive breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%